BIOLOGICAL EVALUATION OF LOCALLY PRODUCED RECOMBINANT PHYTASE IN BROILER CHICKS - F.Sabir; M.Tayyab; A.R.Awan; B.Muneer; A.S.Hashmi; M.Wasim andS.Firyal (Journal of Animal and Plant Sciences, 2018)
Currentstudydealswiththeproductionoflocallycharacterizedrecombinantthermostablephytasefrom Thermotoga naphthophila(PHY )anditsbiologicalevaluationinpoultrybroilerchicks.ThePHY wasproducedfrom16-literLB TN TN mediumusingBL21CodonPluscellshavingpET-21acontainingphytasegenefrom Thermotoga naphthophila.Atotal of135birdsweredividedinto5groupseachhaving27birds.GroupAservedasnegativecontrol,groupB,CandD weregivenfeedsupplementedwith500,1000and1500IU/kgoflocallyproducedrecombinantphytasewhilegroupE servedaspositivecontrol.Theresultsdepictedthatlocallyproducedrecombinantphytaseshowedsignificanteffecton birdsweightgain,feedintakeandfeedefficiencyratio.Presenceof1000IU/kgofphytaseresultedintheweightgainin rd th th 3 ,4 and5 weekoftrialfrom504.77±1to533.53±1.4,767.9±2to823.73±2.84and999.8±7.66to1122.8±2g respectivelywhencomparedwiththecontrol.ThegroupB,CandDshowedanaveragefeedintakeof2710,2780and 2790gascomparedto2669gforgroupA.Thesupplementationof1000IU/kgoflocallyproducedphytaseinfeed resultedintheimprovementoffeedconversionratiofrom2.6to2.4.ThestudydemonstratedthatPHY issuitablefor TN poultryfeedindustryanditsdomesticproductionwillcontributeintheeconomicavailabilityoflocallyproducedphytase forthepoultryfeedindustry. TN supplementationinmonogastricdiets.Thefeedpelleting
Keywords: PHY; PoultryTrial; RecombinantThermostablePhytase; Thermotoga naphthophila; Phytate